Colonization and Cultural Values of Yorùbá People: A Case of Traditional Drums in Yorùbá Land - ALÁDÉSANMÍ Ọmọ́bọ́lá Agnes (Universitas Sanata Dharma, 2019)
Culture is one of the marks by which a community of people of a nation is normally identified. Culture is a phenomenon that distinguishes one ethnic tribe from the other. Various cultures can be identified among the people that are found in a particular community setting. Some cultures can be similar among different people but cultures that differ one from the other are peculiar to people of various tribes. Culture and tradition are sometimes used interchangeably. However, these two concepts have some differences. Tradition is rooted in religious beliefs of a people while culture is embedded in the social activities and social values of a people. Culture is multi-dimensional. Among the Yorùbá ethnic group of South Western Nigeria, there are different cultures that can be identified. Some of these cultures include but not limited to: tribal marks, mode of greetings, dressing/hairstyle and music in which drums are embedded. The focus of this paper is on the use of traditional drums among the Yorùbá. The paper shall examine the origin of drum beating, types of drums and the type of drum beating that is peculiar to each activity and the phenomenon of drum beating in the past and now. The paper discusses the influence the modern technological development has brought into the issue of traditional drums both in positive and negative ways. The paper concludes that this culture is gradually fading away among the Yorùbá people and observed that this is due to the fact that not much value is placed on Yorùbá culture anymore and this is very inimical to the socio-cultural belief of the people.